Emotional labour strategies as mediators of the relationship between public service motivation and job satisfaction in Chinese teachers. (26th November 2014) - Li, Mingjun; Wang, Zhenhong
Abstract: The purpose of this study was to examine the relationship between teachers' public service motivation (PSM) and their job satisfaction levels and to investigate the mediating effects of surface acting (SA) and deep acting (DA) on that relationship. The teacher PSM scale, as well as emotional labour strategies and intrinsic satisfaction (IS) and extrinsic satisfaction (ES) scales, were administered to 317 primary and middle school teachers. Results indicated that PSM among Chinese teachers was significantly and positively related to both IS and ES. Furthermore, structural equation modelling analysis showed that SA and DA played mediating roles in the PSM‐IS and PSM‐ES relationships, respectively. These findings provide a new perspective that explains the mechanism underlying the association between PSM among teachers and their job satisfaction levels. Finally, the possible explanations and implications are discussed.